2021
DOI: 10.1016/j.jbc.2021.101295
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan (W) at position 37 of murine IL-12/IL-23 p40 is mandatory for binding to IL-12Rβ1 and subsequent signal transduction

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Although the pleiotropic immunoregulatory landscape for IL-12 and IL-23, including their role in physiology and disease, have been examined in detail over the past 2 decades ( Wojno et al., 2019 ), our understanding of the structural determinants for the assembly of their promiscuous receptor complexes is incomplete. The current view has been derived from recent structural breakthroughs on complexes mediated by IL-23 and IL-12 ( Bloch et al., 2018 ; Glassman et al., 2021 ), and structure-driven mechanistic interrogation ( Esch et al., 2020 ; Floss et al., 2020 ; Georgy et al., 2021 ). However, it is now clear that this cannot universally apply to the entire family due to fundamental differences in the type and pairing of α- and β-cytokine subunits and the domain organization and pairing of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pleiotropic immunoregulatory landscape for IL-12 and IL-23, including their role in physiology and disease, have been examined in detail over the past 2 decades ( Wojno et al., 2019 ), our understanding of the structural determinants for the assembly of their promiscuous receptor complexes is incomplete. The current view has been derived from recent structural breakthroughs on complexes mediated by IL-23 and IL-12 ( Bloch et al., 2018 ; Glassman et al., 2021 ), and structure-driven mechanistic interrogation ( Esch et al., 2020 ; Floss et al., 2020 ; Georgy et al., 2021 ). However, it is now clear that this cannot universally apply to the entire family due to fundamental differences in the type and pairing of α- and β-cytokine subunits and the domain organization and pairing of receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The mucosal increase in IL-12 during intestinal inflammation has also been observed [54]. It has been shown that SER, HIS and TYR are required for IL-2 binding and biological activity, and that ASP, THR, and TRP are among the important amino acids for the interaction of IL-12 with its receptor [55]. Therefore, controlling these residues may have the potential to be considered a therapeutic target for CD patients, but this needs to be confirmed in further studies [56,57].…”
Section: Discussionmentioning
confidence: 93%
“…The mucosal increase of IL-12 during intestinal inflammation has also been observed [66]. It has been shown that SER, HIS and TYR are required for IL-2 binding and biological activity, and ASP, THR, and TRP are among the important amino acids for the interaction of IL-12 with its receptor [67]. So might controlling these residues have the potential to be considered as therapeutic targets for CD patients, which needs to be approved in further studies [68].…”
Section: Discussionmentioning
confidence: 95%